Ethylenediamine-modified amyloid fibrils of hen lysozyme with stronger adsorption capacity as rapid nano-biosorbents for removal of chromium(vi) ions. Issue 108 (9th November 2016) - Leung, Wai-Hong; So, Pui-Kin; Wong, Wai-Ting; Lo, Wai-Hung; Chan, Pak-Ho
Abstract : The development of amine-fortified amyloid fibrils of hen lysozyme as biosorbents for Cr(vi ) removal is reported. Through –COO − /ethylenediamine conjugation, the nanofibers have higher net positive charge, offering rapid and stronger charge-based absorption of Cr(vi ). Abstract : We report the development of ethylenediamine-modified amyloid fibrils (nanofibers) of hen lysozyme as rapid nano-biosorbents for removing toxic chromium(vi ) ions in water. Ethylenediamine was covalently conjugated with the –COO − groups on positively charged lysozyme nanofibers through the formation of amide bonds using N -hydroxysuccinimide (NHS) and 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC) as the activating agents. Mass spectrometric results indicate that about 42% of lysozyme molecules in nanofibers are conjugated with ethylenediamine. The resulting ethylenediamine-modified lysozyme nanofibers, which have higher net positive charges as a result of the reduction in the number of –COO − groups through ethylenediamine conjugations, can adsorb Cr(vi ) (existing as negatively charged chromate) rapidly in water and have stronger Cr(vi ) adsorption capacity in acidic, neutral and alkaline media (pH 3.0–11.0) compared to unmodified lysozyme nanofibers. Results of the Langmuir isotherm model reveal that the adsorption sites on modified lysozyme nanofibers have higher affinity for Cr(vi ) with respect to those on unmodified lysozyme nanofibers. Ethylenediamine-modified lysozyme nanofibers can maintain their Cr(vi ) removal efficiency (∼60%) after undergoing a series of desorption steps using NaCl as the desorbing agent. Ethylenediamine/–COO − conjugations can increase the adsorption capacities of lysozyme nanofibers for Cr(vi ) in industrial wastewater ( q e = 0.68 mg g −1 ) and river water ( q e = 1.90 mg g −1 ) compared to those of unmodified lysozyme nanofibers ( q e = 0.40 and 1.44 mg g −1 for industrial wastewater and river water, respectively).